Factors Affecting the Growth of SME Sales in the Tourism Sector of Tanjungpinang City - Muhammad Fachri Riauan; Hendy Satria; Andres Putranta Sitepu; Aulia Dewi Gizta; Sri Kurnia (Future Science, 2024)
The aim of research is to determine the influence of e-payment, makloon, and sales promotion on sales growth of SMEs in the tourism sector in Tanjungpinang. The research involved a sample of 91 respondents using the slovin technique. The method used in this research is a quantitative method. The research object consists of small and medium enterprises (SMEs) operating in the tourism sector in Tanjungpinang City. Data collection wa carried out through respondents filling out questionnaires. The research results indicate that partially, e-payment has a significant impact on sales growth, makloon (outsourcing) influences but not significantly on sales growth, and sales promotion significantly influences sales growth. Simultaneously, it is shown that e-payment, makloon, and sales promotion collectively have a simultaneous impact on sales growth.